Impact of health research capacity strengthening in low- and middle-income countries: the case of WHO/TDR programmes. - Happiness Minja; Christian Nsanzabana; Christine Maure; Axel Hoffmann; Susan Rumisha; Olumide Ogundahunsi; Fabio Zicker; Marcel Tanner; Pascal Launois (Public Library of Science (PLoS), 2011)
BACKGROUND: Measuring the impact of capacity strengthening support is a priority for the international development community. Several frameworks exist for monitoring and evaluating funding results and modalities. Based on its long history of support, we report on the impact of individual and institutional capacity strengthening programmes conducted by the UNICEF/UNDP/World Bank/WHO Special Programme for Research and Training in Tropical Diseases (TDR) and on the factors that influenced the outcome of its Research Capacity Strengthening (RCS) activities. METHODOLOGY AND PRINCIPAL FINDINGS: A mix of qualitative and quantitative methods (questionnaires and in-depth interviews) was applied to a selected group of 128 individual and 20 institutional capacity development grant recipients that completed their training/projects between 2000 and 2008. A semi-structured interview was also conducted on site with scientists from four institutions. Most of the grantees, both individual and institutional, reported beneficial results from the grant. However, glaring inequities stemming from gender imbalances and a language bias towards English were identified. The study showed that skills improvement through training contributed to better formulation of research proposals, but not necessarily to improved project implementation or communication of results. Appreciation of the institutional grants' impact varied among recipient countries. The least developed countries saw the programmes as essential for supporting basic infrastructure and activities. Advanced developing countries perceived the research grants as complementary to available resources, and particularly suitable for junior researchers who were not yet able to compete for major international grants. CONCLUSION: The study highlights the need for a more equitable process to improve the effectiveness of health research capacity strengthening activities. Support should be tailored to the existing research capacity in disease endemic countries and should focus on strengthening national health research systems, particularly in the least developing countries. The engagement of stakeholders at country level would facilitate the design of more specific and comprehensive strategies based on local needs.